2017
DOI: 10.1002/pssa.201700440
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Resistive, Capacitive, and Synaptic Properties of Forming Free TiO2‐x‐Based RRAM Devices by Embedded Pt and Ta Nanocrystals

Abstract: The incorporation of metal nanocrystals (NCs) within TiO 2-x thin films offers great advantages for adjusting a wide range of non-volatile memory properties, ranging from resistive and capacitive switching to synaptic capabilities. In this study, it is demonstrated that by inserting very small NCs (%3 nm diameter) of either Pt or Ta, resistance changes over six orders of magnitude and capacitance changes over two orders of magnitude can be induced, with promising variability due to the local enhancement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Resistive random accesses memories (RRAMs) are considered as one of the most promising NVM . A number of research groups have reported synaptic simulation using RRAM devices. It is found that RRAM possesses several advantages for the mimic of biological synapses, such as good data retention (10 years), excellent memory (100 On/Off ratio), excellent scalability (10 nm), and multilevel analogue memory characteristics (∼5 bit or 32 levels). However, analog switching with multilevel states and reliability still have issues for RRAM.…”
Section: Introductionmentioning
confidence: 99%
“…Resistive random accesses memories (RRAMs) are considered as one of the most promising NVM . A number of research groups have reported synaptic simulation using RRAM devices. It is found that RRAM possesses several advantages for the mimic of biological synapses, such as good data retention (10 years), excellent memory (100 On/Off ratio), excellent scalability (10 nm), and multilevel analogue memory characteristics (∼5 bit or 32 levels). However, analog switching with multilevel states and reliability still have issues for RRAM.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is also in line with the experimental data of the retention performance ( Figure 4 b), thus highlighting the acceptable behavior of our prototype. Additionally, in our previous work, we have dealt with similar issues, regarding the charge transfer properties of Pt and Ta NCs within the TiO 2 dielectric matrix [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micromachines 2021, 12, x 14 of 18 with similar issues, regarding the charge transfer properties of Pt and Ta NCs within the TiO2 dielectric matrix [61].…”
Section: Discussionmentioning
confidence: 99%
“…40) Along these lines, TiO 2-x -based bilayer devices were fabricated by employing a room-temperature technique, 41,42) while the impact of the embedded Pt NPs was also explored. [43][44][45] A schematic illustration of the fabricated devices is presented in Fig. 1, while a thin film of pure Ti (4 nm) was used as an oxygen scavenging layer to enhance the stability of the switching effect.…”
Section: Analog Conductance Tuning With Bilayer and Trilayer-based Vc...mentioning
confidence: 99%